Governance of The Corporate Social Responsibility (CSR) Program of Karang Mukti Village in The Development of Embung Batu Beureum Tourism - Samsudin, Samsudin; Hamidi, Muhammad Rifqi; Furrie, Wulan (CV. Publikasi Indonesia, 2024)
This reseach aims to analyze the governance of Corporate Social Responsibility (CSR) programs implemented in Karang Mukti Village in the context of Embung Batu Beureum tourism development. Embung Batu Beureum Tourism is one of the important assets of the village in increasing community income, as well as preserving nature and local culture. CSR has a crucial role in supporting the success of this tourism development program. The methodology of this research uses a qualitative approach, with data collection through in-depth interviews, field observations, and document analysis related to CSR that has been carried out in Karang Mukti Village. The results showed that the governance of CSR programs in Karang Mukti Village has played an important role in supporting the development of Embung Batu Beureum tourism. Karang Mukti Village routinely monitors and evaluates CSR programs that have been implemented. This allows continuous improvement and adjustment of the program according to the needs of the community and tourism developments.